PLANNING OF ATHLETE'S VILLAGE IN WONOSOBO WITH A GREEN ARCHITECTURE APPROACH - Romadhoni, Desika; Muafani; Hendriani, Adinda Septi (Nacreva Publisher, 2025)
This paper presents the planning of an Athlete’s Village in Wonosobo, Central Java, using a green-architecture approach to deliver high-quality temporary housing and training facilities while minimizing environmental impacts. The study combines literature review, field observation, and comparative analysis of established athlete housing precedents (e.g., Kemayoran and Jakabaring) with site appraisal and space-requirement programming. The proposed scheme organizes the 1-ha site into clear functional precincts—accommodation and training, management and support, utilities and waste, and visitor/public interface—linked by legible, barrier-free circulation. Passive design is prioritized through cross-ventilation, daylighting, strategic orientation, and a robust green/open-space network; active systems are limited to targeted, high-efficiency equipment. Resource strategies include rainwater harvesting, low-impact materials, and waste-to-resource handling (segregation, hygienic collection, and landscape-based polishing). The outcome is a context-responsive layout that improves athlete comfort and performance, strengthens operational safety and maintainability, and positions Wonosobo as a competitive-sports hub that models environmentally responsible development. The work’s contribution is a replicable planning framework for medium-scale athlete housing in Indonesian secondary cities, coupling spatial programming with green-infrastructure tactics that are feasible under local climatic, managerial, and budgetary constraints.